Homogenization of Spectral Problem on Small-Periodic Networks - Krylova, A.S.; Sandrakov, G.V. (Журнал математической физики, анализа, геометрии, 2012)
The homogenization of a spectral problem on small-periodic networks with periodic boundary conditions is considered. Asymptotic expansions for eigenfunctions and corresponding eigenvalues on the network are con- structed. The theorem is proved which is a justi¯cation of the asymptotic expansions for some eigenvalues and eigenfunctions of the problem on the network.